Maintaining compliance at home: Helping the elderly with their medications - E Mokgele; PP du Rand (AOSIS, 2000)
The elderly population consumes more drugs for their chronic conditions compared to any age group. In this study it was indicated that the average elderly takes two to four drugs per day. The high quantity and wide range of drugs used by the elderly can lead to significant risks. Adding to the risks is the problem of compliance. Areas of concern regarding safety in administering medications to the elderly are the need for increased awareness of the effects of drugs in their systems.